Dimensões da mediação da informação nos programas e projetos da Rede Cuca - Rodrigues, Denise Marques (2023)
The Cuca Network is part of a public policy that seeks to interact with young people on the outskirts of Fortaleza through various social projects and programs. The starting question is: How are the dimensions of information mediation worked on using interactionist practices and cultural practices with a focus on social protagonism in the programs and projects of the Cuca Network? The general objective of the research is to analyze interactionist practices and cultural practices, based on the dimensions of information mediation in the programs and projects of the Cuca Network. The specific objectives are: a) to present the interactionist and cultural practices that are worked on in the programs and projects of the Cuca Network with a focus on social protagonism; b) to identify which dimensions of information mediation are present in the actions of the programs and projects of the Cuca Network and how they are developed; c) to analyze the contributions of the dimensions of information mediation in the process of developing and strengthening social protagonism in the programs and projects of the Cuca Network. The theoretical framework covers the following themes: information mediation, dimensions of information mediation, interactionist practices, cultural practices and social protagonism. The research methods used were exploratory documentary research of a qualitative nature. Participant observation and documents relating to the Cuca Network's programs and projects were used to collect data, which was analyzed using content analysis. It is considered that the dimensions of information mediation combined with learning tools, such as interactionist and cultural practices, can be instruments that facilitate and enable social protagonism. It is suggested that a new project be developed that includes the dimensions of mediation together. The expectation is that projects like these will be recognized as instruments that make social protagonism a reality, contributing with the potential to have a positive impact on society, allowing for the formulation of new policies, programs or interferences that promote well-being, equality and social justice.